Solve for z 18+6(z-3)=5z+1

Math
18+6(z-3)=5z+1
Simplify 18+6(z-3).
Tap for more steps…
Simplify each term.
Tap for more steps…
Apply the distributive property.
18+6z+6⋅-3=5z+1
Multiply 6 by -3.
18+6z-18=5z+1
18+6z-18=5z+1
Combine the opposite terms in 18+6z-18.
Tap for more steps…
Subtract 18 from 18.
6z+0=5z+1
Add 6z and 0.
6z=5z+1
6z=5z+1
6z=5z+1
Move all terms containing z to the left side of the equation.
Tap for more steps…
Subtract 5z from both sides of the equation.
6z-5z=1
Subtract 5z from 6z.
z=1
z=1
Solve for z 18+6(z-3)=5z+1

Meet the Team our Math Expers

Our Professionals

Robert Kristofer

Anna Frok

Magnus Flores

Lydia Fran

We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

We can solve all your math problems
Scroll to top